Maternal investments in children: The role of expected effort and returns - Sonia R. Bhalotra; Adeline Delavande; Paulino Font Gilabert; Joanna Maselko (University of Essex, Institute for Social and Economic Research (ISER), 2020)
We investigate the importance of subjective expectations of returns to and effort costs of the two main investments that mothers make in newborns: breastfeeding and stimulation. We find heterogeneity across mothers in expected effort costs and expected returns for outcomes in the cognitive, socio-emotional and health domains, and we show that this contributes to explaining heterogeneity in investments. We find no significant heterogeneity in preferences for child developmental outcomes. We simulate the impact of various policies on investments. Our findings highlight the relevance of interventions designed to reduce perinatal fatigue alongside interventions that increase perceived returns to investments.
Keywords: 330; Kinder; Mütter; Ernährung; Soziale Beziehungen; Kognition; Emotion; Gesundheit; Familienökonomik; Pakistan